Vehicle speed guidance strategy at signalized intersection based on cooperative vehicle infrastructure system - Fengyuan JIA; Zhongbing LI; Qingdong CHEN; Xiaolu MA; Qingxi ZENG (Journal of Hebei University of Science and Technology, 2017)
In order to reduce stopping time of vehicle at a signalized intersection, aiming at the difficulty, even the impossibility to obtain real-time queue length of intersection in third and fourth-tier cities in China sometimes, a speed guidance strategy based on cooperative vehicle infrastructure system is put forward and studied. For validating the strategy, the traffic signal timing data of the intersection at Hengshan Road and North Fengming Lake Road in Wuhu is collected by a vehicular traffic signal reminder system which is designed. The simulation experiments using the acquired data are done by software VISSIM. The simulation results demonstrate that the strategy under high and low traffic flow can effectively decrease the link travel-time, reducing average ratio is 9.2 % and 13.0 %, respectively, and the effect under low traffic flow is better than that under high traffic flow. The strategy improves efficiency of traffic at a signalized intersection and provides an idea for the application of vehicle speed guidance based on cooperative vehicle infrastructure system.